Measuring the Effectiveness of Electricity Distribution in Indonesian Provinces using DEA Bootstrap - Amalia Rahmawati; Setyo Tri Wahyudi; Rachmad Kresna Sakti (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2023)
Purpose The aims of this research are to measure the efficiency of electricity distribution in 33 Indonesian provinces from 2010 to 2019. Design/methodology/approach The efficiency was measured using a two-step bootstrap analysis, i.e. DEA BCC and DEA Bootstrap. Findings This study finds that the efficiency estimation uses DEA BCC overestimate and that the proximity between electrical sources and customers becomes one of the supporting factors for the electricity distribution process and reduces losses. Furthermore, workforce input, nameplate capacity, and network length will be adjusted to customers; electricity demand needs as a component of the electricity distribution process from plants to consumers. Research limitations/implications This study uses the output of the number of customers and the amount of electricity distributed while the input variables use the amount of labor, installed capacity, and length of the distribution network. Originality/value This study uses DEA Bootstrap and the variables used in the study is a combination of variables that have been proven to affect electricity distribution and have never been applied in Indonesia.